Analysing creativity, teamwork, and concept understanding on improving learning outcomes in project based learning methods - Rifki Muhendra (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2025)
Higher education faces challenges in improving student learning outcomes, especially in complex concept-based courses such as physics. This study aims to analyse the effect of Project-Based Learning (PBL) method on students' creativity, teamwork, and concept understanding in Basic Physics course. The research method used was an explanatory quantitative design, involving 120 students who were divided into groups to develop a scientific magazine. Data were collected through assessment of the magazines produced and questionnaires measuring the main variables. The results showed that PBL significantly improved students' concept understanding and creativity, although the direct effect of creativity on learning outcomes was not significant. This research contributes to the understanding of the importance of integrating creativity and concept understanding in physics education. The practical implications of this study suggest that the implementation of PBL can enrich students' learning experiences, prepare them for future professional challenges, and encourage the development of important skills such as critical thinking and collaboration. Therefore, it is recommended that higher education institutions adopt PBL as an effective teaching method.